A Compact Vivaldi Shaped Partially Dielectric Loaded TEM Horn Antenna for UWB Communication - Mustafa İlarslan; A. Serdar Türk; Salih Demirel; M. Emre Aydemir; A. Kenan Keskin (International Journal of Antennas and Propagation)
Ultrawideband (UWB) antennas are of huge demand and Vivaldi antennas as well as the TEM horn antennas are good candidates for UWB applications as they both have relatively simple geometry and high gain over a wide bandwidth. The aim of this study is to design a compact antenna that achieves maximum gain over a bandwidth between 1.5 and 10.6 GHz while minimizing its size. The idea is to make use of combined respective advantages of Vivaldi and TEM horn antennas to achieve the desired goals by shaping the TEM horn antenna to look like a Vivaldi antenna. The antenna structure is modified by a dielectric load in the center to increase the gain bandwidth. It is placed in a surrounding box made of PEC material to reduce the undesired side lobes and to obtain more directive radiation pattern. The simulations are performed by using the CST STUDIO SUITE electromagnetic (EM) simulation software and they are later verified by the actual measurements. The Vivaldi shaped partially dielectric loaded (VS-PDL) TEM horn antenna is proposed as a compact UWB antenna for systems using the newly established UWB band and also for the communication systems of popular bands like ISM, Wi-Fi, and GSM.